Assessment of Climate Change on Living Standard: Evidence from Flood-Prone Smallholder Rice Farmers in South-East Nigeria - Nwangwu K. N; Udeh E.A; Chiemela C. J; Onah O. G; Omeje, E. E; Onyia, C. C (International Journal of Integrative Sciences, 2024)
This study seeks to assess the effect of flood on farm household living standard among smallholder rice farmers in southeast, Nigeria. Specifically, the study described the perceived climate hazard occurrence in the study area, analyzed the effect of flood on farm households’ living standards in the study area and described the flood control measures used among smallholder farmers in the study area. Multi-stage random sampling technique was used to select a total sample size of 480 smallholders. Primary data were collected using a well structured questionnaire. Descriptive statistics and OLS regression model were used to analyze the data. The result also showed that majority (90%) of the respondents experienced flooding as the major climate change hazard in the study area. The result of the regression showed that flood reduced rice yield/quantity, flood caused lost of revenue and farm proximity to river negatively significantly influenced the consumption expenditure among smallholder rice farmers at 5 % probability level in the study area. The result also showed that fitting of water inflated sandbags as flood barriers (M= 3.44), creation of drainage (M= 3.28), removal of sediment (M= 3.26), building of water gates (M= 3.22) and construction of flood barrier socks (M= 3.19) were the control measures they used during the incident of flood in the study area